Pengaruh Dampak Corporate Governance Terhadap CorporateSocial Responsibility Disclosure (CSRD) pada Sektor Industri Finance di Indonesia Tahun 2018-2021 - Rivaldi Himawan; Mira Kartika Dewi Djunaedi (UNIVERSITAS KALBIS, 2023)
The purpose of this study is to determine the influence of Good Corporate Governance (GCG) mechanism on Corporate Social Responsibility Disclosure (CSRD) in Indonesia. The Dependent Variable in this study is Corporate Social Responsibility Disclosure, which has scored by how much aspect that reported in CSR disclosure. There are 6 aspects that should be reported. This study categorized as associativeresearch using causal approach. Finance company that listed in Indonesia Stock Exchange on 2018 - 2021 are used as population in this study that downloaded on www.idx.co.id. This study use purposive sampling method for sample gathering with 68 companies. Multiple Regression Analysis is used for analysis method using SPSS version 26 program. The result of this study showing comitee size influencing the Corporate Social Responsibility Disclosure on finance companies that listed in Indonesia Stock Exchange on 2018- 2021